The Design of Diffuse Reflective Off-Axis Surface for Noncircular LED Arrays - Zhen-Min Zhu; Xiang Sun; Bo Peng (IEEE Photonics Journal)
The diffuse reflection light-emitting diode (LED) lighting system is widely used in many areas with its advantages of high uniformity. In order to optimize the lighting performance of noncircular LED arrays, especially illumination efficiency, this paper proposed an off-axis design method for diffuse reflective surface, a mathematical model of a diffuse reflective off-axis surface based on noncircular LED arrays and desired value of the target plane and energy conservation is established. By solving the nonlinear equations, a number of 2-D curves are obtained and use modeling software to combine these 2-D curves into off-axis surface. The results show that the uniformity and efficiency are significantly improved compared with other methods.